Türk Hukukunda Özgürlüğü Bağlayıcı Bir Cezaya Mahkûmiyetin Sonucu Olarak Kişinin Kısıtlanması - Özgenç, Nuri Berkay (Marmara Üniversitesi, 2020)
Ceza mahkûmiyetinin önemli sonuçlarından biri, kişiyi maruz bıraktığı kısıtlılık hâlidir. 4721 sayılı Türk Medeni Kanunu’nun 407. maddesine göre, bir yıl veya daha fazla süreli bir hapis cezasına mahkûm edilmiş olan her ergin kısıtlanır. Kısıtlama; ergin olan ve velayet altında bulunmayan bir kişinin fiil ehliyetinin, kanunda yer alan sebeplere dayalı olarak, mahkeme kararıyla sınırlandırılmasıdır. Kısıtlama kararı tam ehliyetli kişinin ehliyetini sınırlandırır ve onu sınırlı ehliyetsiz hâle getirir. Bir yıl veya daha uzun süreli bir hapis cezasına mahkûm edilmiş olan erginlerin kısıtlanmalarının temelinde, onları ceza infaz kurumlarında bulundukları sırada denetim altında tutmak ve yine bu sırada onların maddi ve manevi çıkarlarını korumak gayeleri yatmaktadır. Mevzuatta kısıtlayarak vasi atama davalarının hızlandırılmasını ve vasilerin hükümlülerin rehabilitasyon süreçlerinde daha aktif roller üstlenmelerini sağlayacak düzenlemeler yapılması, kuruma yeni bir ivme kazandıracaktır.

One of the important consequences of the conviction in criminal courts is the state of the interdiction that the person is exposed to. Pursuant to Article 407 of the Turkish Civil Code numbered 4721, adults who are sentenced to minimum one-year imprisonment are subject to interdiction. The interdiction is limitation of the judicial capacity of the adult person, who is not under custody, based on the reasons specified in the law, by a court decision. The interdiction decision limits the capacity of the fully competent person and renders him - her noncompetent. The purpose of the interdiction of adults who are sentenced to minimum one-year imprisonment is to keep them under control as long as they stay in the penal execution and to protect their material and nonmaterial benefits during this process. Making regulations in the legislation that enables the proceedings on appointment of guardians to be accelerated by restricting and enable the guardians to play more active roles in the rehabilitation processes of the convicts will give the institution a new momentum.
The Interdiction as a Result of being Sentenced to Imprisonment in Turkish Law
Keywords: Hükümlü; Özgürlüğü Bağlayıcı Ceza; Kısıtlılık; Özgürlüğü Bağlayıcı Ceza Sonucunda Kısıtlılık; Vasi; Convicted; Punishment Restricting Freedom; Interdiction; Interdiction as a result of Punishment Restricting Freedom; Guardian